A green and environmentally benign route to synthesizing Z-scheme Bi2S3-TCN photocatalyst for efficient hydrogen production - Yuan, Lang; Yin, Yihang; Xiang, Peng; Shao, Yugui; Gao, Jie; Liu, Jianan; Meng, Huiyuan; Li, Li; Xie, Ying; Xiao, Xudong; Jiang, Baojiang (Frontiers in Chemistry, 2024)
Designing and developing photocatalysts with excellent performance to achieve efficient hydrogen production is one of the important strategies for addressing future energy and environmental challenges. Traditional single-phase photocatalytic materials either have a large bandgap and low visible light response or experience rapid recombination of the photogenerated carriers with low quantum efficiency, which seriously hinders their photocatalytic applications. To solve these issues, an important solution is to construct well-matched heterojunctions with highly efficient charge separation capabilities. To this end, an in-situ sulfurization reaction was adopted after the deposition of Bi 3+ supramolecular complex on layered supramolecular precursor of tubular carbon nitride (TCN).X-ray diffraction (XRD) pattern confirms the as-prepared sample has a good crystalline without any other impurities, while the high-resolution transmission electron microscopy (HR-TEM) reveal the heterojunction possesses a 2D structure with a layer of nano-array outside its surface. Combined with the Fourier-transform infrared (FT-IR) spectra and Energy dispersive X-ray spectroscopy (EDX), the interfacial interactions are revealed. Owing to the formation of the Z-scheme heterojunction, the visible light adsorption and the separation efficiency of the photo-generated carriers are both enhanced obviously, leaving the high energy electrons and high oxidative holes to participate in the photocatalytic reactions. As a result, the photocatalytic hydrogen evolution rate of Bi2S3-TCN achieves 65.2 μmol•g -1 •h -1 . The proposed green and environmentally benign route can also be applied to construct other sulfides with 2D TCN, providing some important information for the design and optimization of novel carbon-nitride-based semiconductors.